Recopilación de cánticos interpretados por el pueblo shuar de la parroquia “bomboiza” del cantón Gualaquiza, en su festividad anual “la fiesta de la chonta”. - Solano Zhiñin, Melyza Soraya (2022)
The shuar people is one of the most important people of our country, reflection of this is the cultural activity so that in this work a general objective was raised: to contribute to the cultural strengthening of the shuar people through the collection of songs interpreted in their festival of the chonta so that it maintains its importance within the cultural identity of Ecuador. The research universe was delimited with a population of eight people made up of two emissaries or heads of shuar community, three people from the shuar people who have knowledge of shuar music and three representatives and in charge of the area of tourism and culture of the municipality of Gualaquiza to whom the interview guide was applied. The results were analyzed in a qualitative way which allowed to determine that the shuar people as such, is disappearing due to the lack of knowledge of their culture by the new generations, even the shuar elders and adults are unaware of the important celebrations of the people and everything that they entail. Given this reality, a document on the most important celebration of the shuar people was prepared; the festival of the chonta, where all the chants interpreted within this celebration are transcribed, this as part of the proposal of the research problem. The methods used in this research were: Scientific Method. – which allowed to develop the bases of the theoretical framework and was present throughout the research. Synthetic Method. – it allowed us to interpret the results of the interviews applied, also helped us to break down the study topic, its variables, conclusions, recommendations, discussion and analysis performed. Analytical Method. – it helped us to analyze the musical notes within the chonta festival chants and then translate them into a score. Hermeneutic Method. – it allowed to make a description in shuar and spanish to the eight phases of the Festival of the Chonta. The proposed derivative of the thesis was presented through an event in where the document has been delivered to the competent authorities of the GAD Municipal de Gualaquiza, accompanied by a vocal demonstration and dance of a group of shuar formed by young people from the same village, this event was held in the hall of the auditorium of the municipality of Gualaquiza and transmitted through the zoom platform, where took part authorities of the same canton, the director of the institute ETSA of the parish Bomboiza, teachers and the general public. We were able to conclude that there is a great need of the shuar people to return to practice their culture, and that the municipal entities support the advertisement and conservation of 13 culture, only in this way will it be possible to stop the problem of globalization that little by little is consuming the Shuar culture. The authorities involved in this investigation recommend to continue working on research projects that contribute to safeguarding the traditions of the various cultures and strengthening the cultural richness of Ecuador.